2021
DOI: 10.3389/fneur.2020.621010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Regression-Based Norms for Cognitive Functioning of Persons With Multiple Sclerosis in an Independent Sample

Abstract: Background: Cognitive impairment is common in multiple sclerosis (MS). Interpretation of neuropsychological tests requires the use of normative data. Traditionally, normative data have been reported for discrete categories such as age. More recently continuous norms have been developed using multivariable regression equations that account for multiple demographic factors. Regression-based norms have been developed for use in the Canadian population for tests included in the MACFIMS and BICAMS test batteries. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We used conventional norms and a raw score change of 4 point (10% change in magnitude) as a clinically meaningful measure 39 to define SDMT progression. However, future studies should investigate whether regression-based norms for SDMT might better detect abnormal performance in patients with MS [58][59][60] and therefore improve the performance of ICA components.…”
Section: Discussionmentioning
confidence: 99%
“…We used conventional norms and a raw score change of 4 point (10% change in magnitude) as a clinically meaningful measure 39 to define SDMT progression. However, future studies should investigate whether regression-based norms for SDMT might better detect abnormal performance in patients with MS [58][59][60] and therefore improve the performance of ICA components.…”
Section: Discussionmentioning
confidence: 99%
“…We also enrolled healthy controls who have been described in detail elsewhere ( 28 ). Briefly, healthy controls were aged 18 years or older.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we used the SDMT ( 39 ) to assess information processing speed, the CVLT-II; Trial 1–5 total recall score ( 40 ) to assess verbal learning and memory, the BVMT-R (summed recall score for all three learning trials) ( 41 ) to assess visual learning and memory, and tests of verbal fluency (letter and animal categories) ( 42 ) to assess language and executive abilities. We converted raw test scores to age-, sex- and education-adjusted z-scores using local regression-based norms because we previously demonstrated that these performed better in our population than other published regression-based norms ( 28 ). Z -scores of ≤-1.5 were classified as impaired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate LGI1-LE-associated neuroanatomical changes in the MTL, the patient’s T1-weighted brain MRI scans were compared intraindividually and qualitatively to the T1-weighted brain MRI scans of n = 12 healthy age-matched controls (i.e., aged 60 years or older) obtained from Marrie et al.’s (2021) Comorbidity, Cognition and Multiple Sclerosis (C-COMS) study. One healthy control was excluded from the volumetric analysis due to a corrupted image file.…”
Section: Case Reportmentioning
confidence: 99%